A Hypothetical Model Proposal for Social Connectednessin Adolescents - Savcı, Mustafa; Aysan, Ferda (My University, 2019)
In this study, the hypothetical model proposed for social connectedness was tested. Firstly, the effect of social intelligence on social anxiety was tested. Then the effect of social anxiety on internet addiction and peer relations was tested. Finally, the effect of internet addiction and peer relations on social connectedness was tested. A hypothesis has been proposed for each effect. This study was conducted on 991 adolescents (578 girls and 413 boys). The hypothetical model was tested in the general sample, the girls and the boy’s sample. As a result of the analysis, the hypothetical model was confirmed in three samples. According to the findings, social intelligence affects social anxiety negatively. Social anxiety affects internet addiction positively but peer relations negatively. Peer relations affects social connectedness positively. Finally, internet addiction affects social connectedness negatively.
Keywords: Davranış Bilimleri